Differences in Growth and Yield of Moringa Oleifera Leaves by Immersing Seeds and Variations of Planting Medium - Rini Sulistiani; Surianto Surianto; Aisar Novita; Sasmita Siregar; Ahmad Fadhillah Rasyidi (Politeknik Negeri Lampung., 2024)
Seeds are generally used for moringa cultivation. However, the seeds produced have a fairly hard seed coat, thus affecting germination and seed vigor. The research by immersing seeds with plant growth regulators (PGR) and a comparison of the composition of planting medium need experimentation to get the maximum PGR concentration and the right composition of the planting medium to grow. The study was conducted using a Split Plot Design with the main plots PGR consisting of Z1 (freshwater), Z2 (Coconut liquid), and Z3 (GA3). The subplot is Plant Medium consisting of M1 (soil: sand: manure-1:1:2); M2 (soil: sand: manure-1:2:1); M3 (soil: sand: manure-2:1:1). Data were examined by Analysis of Variance and continued by DMRT at α 5%. The results of the analysis showed that PGR had a significant effect on plant height, stem diameter, and root length. The composition of the planting medium caused significant differences in plant height, stem diameter, number of leaves, and fresh and dry leaf weight. The interaction between the planting medium and PGR caused differences in stem diameter at 2 and 8 weeks after planting. The recommended PGR treatment is freshwater for longer roots and taller plants. M1 planting media produced the most number and weight of leaves. The combination treatment of Z3M2 produces the largest stem diameter.